Tax Elasticity of Border Sales: A Meta-Analysis - Dat Huynh; Anna Sokolova; Mehmet S. Tosun (Institute of Labor Economics (IZA), 2022)
When regions in close proximity have different tax rates, residents may engage in cross-border shopping and take advantage of tax differentials. The extent of this activity can be captured by the tax elasticity of border sales (TEBS). We collect 749 estimates of TEBS reported in 60 studies, and conduct the first meta-analysis of this literature. We show that the literature is prone to selective reporting: positive estimates of TEBS are systematically discarded—this biases the mean reported estimate away from the 'true' underlying effect. Reported estimates also vary widely; we construct 29 control variables that capture empirical strategies used to obtain them, and employ Bayesian Model Averaging to pin down the sources of this variation. We find that sales of food, retail and fuel are more elastic compared to sales of tobacco and other individual 'sin' products; that while the cross-border shopping is prominent in the US, it is much less prevalent in Europe and other countries.
Keywords: H71; H73; H26; H22; R12; H31; 330; cross-border shopping; taxation; tax elasticity; meta-analysis; Bayesian Model Averaging